2014
DOI: 10.1096/fj.14-260067
|View full text |Cite
|
Sign up to set email alerts
|

Triggering receptor expressed on myeloid cells‐2 fine‐tunes inflammatory responses in murine Gram‐negative sepsis

Abstract: During infections, TLR-mediated responses require tight regulation to allow for pathogen removal, while preventing overwhelming inflammation and immunopathology. The triggering receptor expressed on myeloid cells (TREM)-2 negatively regulates inflammation by macrophages and impacts on phagocytosis, but the function of endogenous TREM-2 during infections is poorly understood. We investigated TREM-2's role in regulating TLR4-mediated inflammation by studying wild-type and TREM-2 2/2 mice challenged with LPS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 66 publications
3
57
0
Order By: Relevance
“…Microglia and macrophage TREM2 expression in vivo and in vitro sharply decline in response to acute proinflammatory stimuli such as lipopolysaccharide (LPS) or tumor necrosis factor (TNF) [51,91,[96][97][98]. One mechanism by which the downregulation of TREM2 mRNA is proposed to occur is through the NF-kB pathway.…”
Section: Regulation Of Trem2 Gene Expressionmentioning
confidence: 99%
“…Microglia and macrophage TREM2 expression in vivo and in vitro sharply decline in response to acute proinflammatory stimuli such as lipopolysaccharide (LPS) or tumor necrosis factor (TNF) [51,91,[96][97][98]. One mechanism by which the downregulation of TREM2 mRNA is proposed to occur is through the NF-kB pathway.…”
Section: Regulation Of Trem2 Gene Expressionmentioning
confidence: 99%
“…Recent studies have shown that Triggering Receptor Expressed on Myeloid cells 2, also known as (TREM2), is an efficient negative regulator of TLR-4 signaling [145][146][147]. TREM2 is a membrane receptor that mediates critical functions of microglia, such as suppression of pro-inflammatory cytokines and promotion of phagocytosis of apoptotic neurons and cell debris [148].…”
Section: Cur and Tlr-4 In Neuroinflammatory Diseasesmentioning
confidence: 99%
“…TREM2 is highly expressed in microglia with approximately 300-fold higher than that in the neuron and other glial cells (Luo et al, 2014;Wu et al, 2015), and acts as a key regulator of inflammatory response (Torika et al, 2016;Choi et al, 2017;Zhong et al, 2017). TLR4 is activated by bacteria to modulate the innate immune responses, which releases pro-and antiinflammatory cytokines to promote robust inflammatory responses (Gawish et al, 2015). TLR4 is activated by bacteria to modulate the innate immune responses, which releases pro-and antiinflammatory cytokines to promote robust inflammatory responses (Gawish et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…TREM-2 down-regulates TLR4-mediated cytokine responses, TNF-a production and the NF-kB activation (Peng et al, 2010;Sharif et al, 2014). TLR4 is activated by bacteria to modulate the innate immune responses, which releases pro-and antiinflammatory cytokines to promote robust inflammatory responses (Gawish et al, 2015). The PI3K is an upstream event of the NF-kB pathway, which is the most important downstream pathway mediated by TLR4.…”
Section: Introductionmentioning
confidence: 99%